"So let me give you money, you give me what I want": decision-making priorities around contraceptive method and source choice among young women in Kenya - Lisa M. Calhoun; Mahua Mandal; Bernard Onyango; Erick Waga; Courtney McGuire; Thomas van den Akker; Lenka Beňová; Thérèse Delvaux; Eliya M. Zulu; Ilene S. Speizer (BMC, 2023)
Abstract Background Many factors influence young women's choice of contraceptive methods and where to source them, yet less is known about whether one of these choices (method or source) is prioritized and the relationship between these choices. This study qualitatively explored decision-making around contraceptive method and source choice among young women in Kenya. Methods In August-September 2019, 30 in-depth interviews were conducted with women ages 18-24 who had used two or more contraceptive methods and resided in three counties: Nairobi, Mombasa or Migori. Participants were recruited from public and private health facilities and pharmacies. Interview guides captured information about decision-making processes for each contraceptive method the respondent had ever used. Responses were audio-recorded, transcribed, translated into English, coded, and analyzed thematically. Results The majority of respondents knew which method they wanted to use prior to seeking it from a source. This was true for all types of methods that women ever used. Of the small number of respondents who selected their source first, most were in the post-partum period or experiencing side effects and sought counseling at a source before choosing a method. Conclusions This study highlights the importance of providing young women with high quality counseling that provides full information about contraceptive options and addresses that young women's needs vary along the reproductive health continuum of care. This will ensure that young women have information to inform future contraceptive decision-making prior to seeking care.